Multiple Choice Questions-Part II (Classification, Item Preparation, Analysis and Banking) - Chaudhary, N; Bhatia, BD; Mahato, SK; Agrawal, KK (Journal of Universal College of Medical Sciences, 2014)
No Abstract Available DOI: http://dx.doi.org/10.3126/jucms.v2i3.11830 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 54-59